High-Fat Diet Increases Serum HDL, but Not for LDL and HDL/LDL Ratio in MICE - Laksana, Iqbal; Rejeki, Purwo Sri; Herawati, Lilik; Arif, Mohammad Anam Al; Wardhani, Indrayuni Lukitra (Folia Medica Indonesiana, 2021)
The use of a ketogenic diet with an increased proportion of fat is rampant lately, both as a therapy or even lifestyle. The use of a ketogenic diet is feared to cause dyslipidemia. It will also lead to atherosclerosis and thrombosis. This study aimed to determine the effect of a high-fat diet on HDL, LDL, and HDL/LDL ratio in mice. Thirty male Mus Musculus, 2-3 mo, 15-25 g divided into five groups diet. K1 (12% fat, 20% protein, 62% carb), K2 (30% fat, 60%protein), K3 (45% fat, 45% protein), K4 (60% fat, 30% protein) and K5 (75% fat, 15% protein) for 4 weeks. Feed and water by adlibitum. Blood for serum was taken from the ventricle, while in the measurement of HDL serum level, the LDL used ELISA. Normality of data analyzed by Shapiro Wilk, and homogeneity by Levene test. HDL serum was analyzed using equality test followed by Games Howell, LDL serum and ratio of HDL/LDL was tested by ANOVA followed by LSD with significance 0,05. HDL serum in K1 (62,50±9.94) mg/dL, K2 (78,40±18,76) mg/dL, K3 (79,00±3,81) mg/dL, K4 (80,00±2,16) mg/dL, and K5 (83,50±5,62) mg/dL with p<0,05 in K1, K2 to K3, K4 and K5. LDL serum in K1 (21,67± 4,80) mg/dL, K2 (23,00±12,70) mg/dL, K3 (18,40±4,34) mg/dL, K4 (24,00 ±1,83) mg/dL and K5 (22,00 ± 4,08) mg/dL with p>0,05. Ratio HDL/LDL K1 (3,01±0,91), K2 (4,10±1,86), K3 (4,53±1,5), K4 (3,35±0,34), and K5 (3,96 ± 1,25) with p>0,05.